LUMPAC : desenvolvimento e aplicação de um pacote computacional para o estudo de estruturas luminescentes a base de Európio - Dutra, José Diogo de Lisboa (2014)
Lanthanide-containing systems have many applications, which extend from the biomedical field to optical images areas. Because of that, such systems have attracted the attention of several research groups around the world. It is indisputable that theoretical tools can provide useful information for the understanding of the phenomena that are not easily explained by using only experimental data. Moreover, the theoretical tools are useful for design new systems. Although several tools for the study of lanthanide complexes have been developed since the early 90 s, their use is still limited on account of these tools not being implemented into a userfriendly, free of charge computational package for the scientific community. In this context, the development of LUMPAC (LUMinescence PACkage) is inserted. With this new tool, we hope to enable experimental research groups to use theoretical tools on projects involving systems that contain lanthanide ions. In this dissertation, the methods implemented into LUMPAC are described in detail, given the user a good understanding of them. A short description on LUMPAC is introduced to provide an overview of the features that are implemented in the package. Furthermore, a detailed manual treating all the modulus of LUMPAC is available as an appendix. The LUMPAC project started in 2008. During its development, the program was applied in many different kinds of study involving lanthanide systems, as will be shown in a chapter of this dissertation. The network of collaboration among the Pople Laboratory with some research groups of prestigious universities allowed all these applications. This way, it is then possible to have an idea about some kinds of study in which the program can be applied. So far, LUMPAC is the only software that enables the study of luminescent properties of lanthanide-containing systems, being available free of charge at the following site: http://www.lumpac.pro.br.